2015
DOI: 10.1007/s10278-015-9836-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Whole Slide Imaging in Dermatopathology

Abstract: Digital whole slide imaging (WSI) is an emerging technology for pathology interpretation, with specific challenges for dermatopathology, yet little is known about pathologists' practice patterns or perceptions regarding WSI for interpretation of melanocytic lesions. A national sample of pathologists (N = 207) was recruited from 864 invited pathologists from ten US states (CA, CT, HI, IA, KY, LA, NJ, NM, UT, and WA). Pathologists who had interpreted melanocytic lesions in the past year were surveyed in this cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Detailed information about development of the cases, participant recruitment, and diagnostic classification is provided elsewhere. [10][11][12][13][14] Histology form and mapping scheme We gathered assessment and recommendations on each case using a standardized online histology form and then classified the diverse terms using the Melanocytic Pathology Assessment Tool and Hierarchy for Diagnosis (MPATH-Dx) histology form. 13 This tool organizes pathologists' diverse descriptive terms of melanocytic skin lesions into five diagnostic classes, with suggested treatment recommendations (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information about development of the cases, participant recruitment, and diagnostic classification is provided elsewhere. [10][11][12][13][14] Histology form and mapping scheme We gathered assessment and recommendations on each case using a standardized online histology form and then classified the diverse terms using the Melanocytic Pathology Assessment Tool and Hierarchy for Diagnosis (MPATH-Dx) histology form. 13 This tool organizes pathologists' diverse descriptive terms of melanocytic skin lesions into five diagnostic classes, with suggested treatment recommendations (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of this study has been reported elsewhere. 12,13 Pathologists eligible for participation had completed their pathology training (residency and/or fellowship), diagnosed melanocytic lesions in practice within the previous year, and expected to continue diagnosing melanocytic lesions for the next 2 years. Eligible pathologists were invited to take part in the study through electronic mail.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the melanoma pathology study (M-Path) are summarized in detail elsewhere. 2,3 In brief, pathologists who interpret melanocytic lesions as part of their clinical practice were recruited to participate in an online survey and test-set interpretation. Approval was obtained from the Institutional Review Board of the University of Washington Human Subjects Division.…”
Section: Methodsmentioning
confidence: 99%